The Relevance of Pancasila Values in the Formation of National Character to Realize a Civil Society in Indonesia - Aflah Labib Hanan; Ghufron Mubarok (Konsultan Jurnal Ilmiah Indonesia, 2025)
Pancasila, as the foundation of the state and the ideology of the Indonesian nation, plays a primary role in shaping the character of its citizens. Its values ​​serve as moral and social ethical guidelines relevant to facing the challenges of globalization and the national identity crisis. This study aims to analyze the relevance of Pancasila values ​​in shaping national character and its contribution to the realization of a civil society in Indonesia. The research method used was a literature review, examining various academic sources related to Pancasila, character education, and civil society. The results indicate that Pancasila values ​​can strengthen moral integrity, foster national awareness, and shape just and civilized social behavior. Thus, Pancasila holds a strategic position in national character development, oriented towards the creation of a just and civilized civil society.